mRNA display with library of even-distribution reveals cellular interactors of influenza virus NS1 - Yushen Du (Nature Portfolio, 2020)
Identification of low abundance proteins interacting with viral proteins can be challenging. Here, Du et al. develop an mRNA display approach with a library of even distribution, identify host proteins interacting with NS1 protein of influenza A virus, and show that one interactor provides a means to regulate cellular fatty acids synthesis.